Pelatihan Pembacaan Wawancan dan Pisaan bagi Guru Bahasa Lampung Jenjang SMA Se-Kota Bandarlampung - Iqbal Hilal; Kahfie Nazaruddin; Ali Mustofa; Khoerotun Nisa Liswati; Yinda Dwi Gustira (Nuwo Abdimas, 2022)
This training aims to provide insight and understanding to Lampung language teachers throughout Bandarlampung about oral traditions, especially interview and piasan. The benefits obtained through this service are that it can improve abilities and skills in reading and developing the oral tradition of interviewing and piasan. in the context of maintaining and preserving the oral tradition of wawancan and piasan in Lampung Province. This service activity was carried out at FKIP, University of Lampung, involving all Regional Language Subject Teachers in Bandar Lampung City. The method used in this training is the work instruction training method. The number of participants for this training is 20 teachers who are members of the Lampung Language and Script MGMP throughout Bandar Lampung City. The success of this activity is measured by the assessment of results and processes. The success of this training is measured by evaluating the performance of reading interviews and writings by individual trainees. Furthermore, the process assessment is measured through an instrument in the form of a questionnaire that focuses on the aspects of the usefulness and success of the training implementation, which includes both training materials and training facilities and infrastructure. After participating in the training on reading interviews and writings, the competence of the teachers in reading interviews and writings has increased..